2011
DOI: 10.1002/mc.20834
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐9 receptor gene is transcriptionally regulated by nucleolin in T‐Cell lymphoma cells

Abstract: Interleukin-9 (IL-9) is a multifunctional cytokine that not only has roles in immune and inflammatory responses but also is involved in growth-promoting and anti-apoptotic activities in multiple transformed cell lines, which suggests a potential role in tumorigenesis. Over-expression of the receptor of IL-9 (IL-9R) occurs in several types of human leukemias and in radiation-induced mouse T-cell lymphoma (TL). The molecular mechanism that regulates transcription of the IL-9R gene (Il9r) during leukemogenesis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
(26 reference statements)
2
13
0
Order By: Relevance
“…The results of the present study demonstrate that the association between P-nucleolin expression and survival status is different from that between P-nucleolin expression and overall survival. Previous studies have demonstrated that nucleolin regulates a number of cancer-associated factors and directly or indirectly participates in tumorigenic pathways (28,29). Therefore, the role of P-nucleolin in cancer should be comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrate that the association between P-nucleolin expression and survival status is different from that between P-nucleolin expression and overall survival. Previous studies have demonstrated that nucleolin regulates a number of cancer-associated factors and directly or indirectly participates in tumorigenic pathways (28,29). Therefore, the role of P-nucleolin in cancer should be comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Its predominant localization in the nucleus relates to the fundamental role of this protein in RNA and DNA metabolism 239 . At the intracellular level, nucleolin acts as a transcriptional factor of several oncogenes and provides transcriptional regulation for mRNA of pro-tumorigenic proteins 266,267,269,286,290,291,466 . On the cell-surface, nucleolin has been described as a binding partner for ligands with fundamental roles in tumorigenesis and angiogenesis 240,[303][304][305]318,319 .…”
Section: Introductionmentioning
confidence: 99%
“…Human nucleolin is a 707-amino acid protein consisting of an acidic histone-like N terminus, a central domain containing four RNA binding domains, and a C terminus that is rich in arginine and glycine. This multidomain structure reflects the diverse roles of nucleolin in cell growth, proliferation and death (Ginisty et al, 1999;Srivastava and Pollard, 1999;Shang et al, 2011). Although nucleolin has been generally considered a predominantly nucleolar protein, it appears to be very mobile and can also be present in the nucleoplasm and cytoplasm and on the cell surface (Daniely and Borowiec, 2000;Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 97%